An ab initio investigation of the structural, mechanical, electronic, optical, and thermoelectric characteristics of novel double perovskite halides Cs2CaSnX6 (X = Cl, Br, I) for optically influenced RRAM devices. Issue 16 (11th April 2023) - Kiran, Saira; Mumtaz, Umair; Mustafa, Aymen; Imran, Muhammad; Hussain, Fayyaz; Rasheed, Umbreen; Khalil, R. M. A.; Khera, Ejaz Ahmad; Nazir, Alia
Abstract : Hybrid lead halide perovskites have been considered as promising candidates for a large variety of optoelectronic applications. Abstract : Hybrid lead halide perovskites have been considered as promising candidates for a large variety of optoelectronic applications. By exploring novel combinations of lead-free double perovskite halides, it is possible to find a suitable replacement for poisonous lead halide perovskites, enhancing electronic and optical response for their application as optically-influenced resistive switching random access memory (RRAM). In this work, the structural, mechanical, elastic, electronic, optical, and thermoelectric characteristics of lead-free double halide perovskites were investigated by Vienna ab initio simulation package (VASP) to explore their role in RRAM. From the analysis of mechanical constraints, it is clear that all three composites of Cs2 CaSnX6 (X = Cl, Br, I) are mechanically stable and ductile in nature. The electronic bandgap with and without spin–orbit coupling (SOC), and total and sub-total density of states (TDOS, sub-TDOS) have been calculated using the Perdew–Burke–Ernzerhof generalized gradient approximation (PBE-GGA) potentials. The observed direct band gaps of 3.58 eV, 3.09 eV, and 2.60 eV for Cs2 CaSnCl6, Cs2 CaSnBr6, and Cs2 CaSnI6, respectively, reveal the suitability of these specified composites as resistive switching material for RRAM devices. Additionally, the optical characteristics, such as complex refractive index, absorption coefficient, and reflectivity of the compounds under consideration have been calculated under the action of incident photons of 0 to 14 eV energy. The thermoelectric properties of Cs2 CaSnX6 (X = Cl, Br, I) double perovskite halide were computed and analyzed with the help of the BoltzTraP Code.